Critical Discourse Analysis of the ‘Indonesia Gelap’ Issue on the Meet Nite Live TikTok Account: Dissecting Political Narratives in the Social Media Era - Sarwatul Mufidah; Risna; Abdul Haliq (The Future of Education Journal, 2025)
The expression “Indonesia Gelap” emerged on social media as a satirical critique of systemic corruption and governance failures in Indonesia under the administration of President Prabowo Subianto and Vice President Gibran Rakabuming Raka, quickly gaining traction among younger audiences through the Meet Nite Live TikTok account. This study aims to uncover how the “Indonesia Gelap” narrative is constructed, disseminated, and consumed within the TikTok platform. Employing a descriptive qualitative design grounded in Fairclough’s three‐stage Critical Discourse Analysis (textual, discursive, and social practice), data were collected via digital observation and documentation of videos tagged #IndonesiaGelap, followed by systematic pre‐selection based on lexical frequency, virality metrics, and political relevance. Findings reveal that the narrative utilizes sports metaphors such as “liga korupsi” and “season baru PLN kesetrum” and hyperbolic language “token listrik, silau, Indonesia” to frame corruption as an endless, dramatized spectacle, while strategic tagging and timing leverage TikTok’s For You Page algorithm to achieve high engagement (10.7 K likes, 499 comments, 893 saves, 1 696 shares). At the social level, the hashtag functions both as collective expression of moral outrage and as a mobilizing symbol of ideological resistance. Limitations include the single‐account focus and qualitative scope; future research should broaden platform and creator samples and integrate mixed methods to measure long‐term impact on political perceptions.